Evaluation of the anaerobic ability of alpine skiing skiers through the slalom simulator - Vasilios Giovanis; Panagiotis Vasileiou (Physical Education of Students, 2017)
Purpose: The purpose of the research was the evaluation of efficiency of anaerobic ability (power), anaerobic endurance, anaerobic fatigue and the restitution of the pulse rate of alpine skiing students through the slalom simulator. In addition, the aim of the research was the correlation of the special tests of alpine skiing on dry ground (octagon test) and in snow (triangle test and slalom test) with the target of determining ability levels. Methods: The 20 people sample was composed by two teams of male and female who took the course for advanced (n = 7) aged 23±1.40 years and for beginners course (n = 13) aged 20±1.49 years. For the evaluation process two special tests were used, on the ground and in snow. The ground test was completed in the slalom simulator for 40 seconds. The second ground test was the octagon bouncing (40cm each side) x 3. The snow test was the Haczkiewicz test (triangle test) and the slalom (7 gates), where the time of a try was measured. Results: The best efficiency in anaerobic power was made by the advanced males and females, while in the anaerobic endurance by the beginners males and females. The best performance in the dexterity tests in snow on the triangle and slalom test was made by the advanced males and beginners females respectively. Conclusions: The significant correlation between the results of anaerobic performance in the slalom simulator and the triangle test in snow confirms the means of diagnosing skill and fitness on dry ground and snow respectively. There is a significant correlation between snow test results and there is no correlation with the octagon test. The aforementioned results can be used in the talent selection process of alpine skiing.